2015
DOI: 10.1007/s00405-015-3643-4
|View full text |Cite
|
Sign up to set email alerts
|

Speech understanding in noise with the Roger Pen, Naida CI Q70 processor, and integrated Roger 17 receiver in a multi-talker network

Abstract: Roger is a digital adaptive multi-channel remote microphone technology that wirelessly transmits a speaker’s voice directly to a hearing instrument or cochlear implant sound processor. Frequency hopping between channels, in combination with repeated broadcast, avoids interference issues that have limited earlier generation FM systems. This study evaluated the benefit of the Roger Pen transmitter microphone in a multiple talker network (MTN) for cochlear implant users in a simulated noisy conversation setting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 19 publications
2
23
0
3
Order By: Relevance
“…Because of the increased distance of the speakers to the MM the SNR will decrease, whereby speech perception, even with the MM, will become difficult. This is comparable with the results of de Ceulaer et al (2015) who used a multiple talker network test set up with three speech sources to simulate a group conversation. They found only a limited improvement in SRT when using one Phonak Roger Pen, but a considerable improvement by using three Roger Pens.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Because of the increased distance of the speakers to the MM the SNR will decrease, whereby speech perception, even with the MM, will become difficult. This is comparable with the results of de Ceulaer et al (2015) who used a multiple talker network test set up with three speech sources to simulate a group conversation. They found only a limited improvement in SRT when using one Phonak Roger Pen, but a considerable improvement by using three Roger Pens.…”
Section: Discussionsupporting
confidence: 78%
“…By acquiring the signal at or near the source, the SNR at the listener's ear is improved and consequently the negative effects of ambient noise, as well as those of distance and reverberation, are reduced. Previous research has shown considerable improvement in unilateral CI users' speech recognition in noise using RF systems (Schafer & Thibodeau, 2004, Schafer et al, 2009de Ceulaer et al, 2015). These studies are laboratory studies with a multiple loudspeaker set up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are other concerns as well. Although there are numerous studies showing the benefit of RM technology for individuals with CIs, there is a lack of information specifically with the use of the Cochlear MM21 (Fitzpatrick et al, 2009;Wolfe et al, 2013;De Ceulaer et al, 2016). It is beyond the scope of this article to dissect all of these questions, but further research in these areas is necessary.…”
mentioning
confidence: 97%
“…De Ceulaer et al 5 recognized the need to improve communication in group settings and evaluated the benefit of the Roger Pen transmitter microphone in a multitalker network with CI users. Using the Naida Q70 CI and Phonak-integrated Roger 17 receivers, 12 adults repeated sentences from a Flemish sentences-in-noise test presented randomly from one of three speakers to simulate a small group conversation in multitalker babble noise.…”
Section: Introductionmentioning
confidence: 99%